Die plek en funksie van topologie as teologiese belangeruimte in die struktuur van die Matteus-evangelie - Volschenk, G. J. (HTS teologiese studies, 2003)
The place and function of topology as theological point of interest in the structure of the Gospel of MatthewThis article focuses on the place and function of topology within the structure of Matthew. An overview of the different models on the struc-ture of Matthew shows the dominance of the chiastic model. The author uses the topological-chiastic model to illustrate the significance of the landscape and topology in the Gospel of Matthew. The aim of the article is to emphasize the significance of house, land and topology in Matthew’s Gospel from a theological perspective. The conclusion is that there is a relationship between the chiastic structure of Matthew and the topological movement in the plot of Matthew.